Catching up in the global wine industry: innovation systems, cluster knowledge networks and firm-level capabilities in Italy and Chile. (3rd July 2007) - Bell, Martin; Giuliani, Elisa
This paper is about technological learning in wine producing clusters in Italy and Chile. It raises questions about policy measures to strengthen knowledge-centred interactions in cluster innovation systems. It shows that strong intra-cluster networks cannot be assumed to exist simply because firms share geographically bounded locations. Instead, networks are shaped by the firms' knowledge resources. Second, the effectiveness of knowledge transfer links from PRTOs to cluster firms depends heavily on characteristics of the intra-cluster knowledge network, in particular on the extent to which the firms are connected within the cluster via gatekeeper and broker roles. Implications for policy are noted.